2022
DOI: 10.1039/d2ta01931k
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient oxygen evolution catalysis achieved by NiFe oxyhydroxide clusters anchored on carbon black

Abstract: The sluggish kinetics of oxygen evolution reaction restricts the efficiency of renewable energy storage and conversion devices including water splitting and metal-air battery. Owing to their rich misaligned atoms and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…The charge-transfer resistance ( R ct ) for ANCO-1, ANCO-2, and ANCO-3 is 52.3, 40.2, and 78.3 Ω, respectively. The lowest R ct for ANCO-2 reveals that ANCO-2 has the lowest interfacial charge transfer and kinetic resistance …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The charge-transfer resistance ( R ct ) for ANCO-1, ANCO-2, and ANCO-3 is 52.3, 40.2, and 78.3 Ω, respectively. The lowest R ct for ANCO-2 reveals that ANCO-2 has the lowest interfacial charge transfer and kinetic resistance …”
Section: Resultsmentioning
confidence: 99%
“…The lowest R ct for ANCO-2 reveals that ANCO-2 has the lowest interfacial charge transfer and kinetic resistance. 62 The ECSA normalized current can better reflect the intrinsic catalytic activity of the catalysts compared with the geometric area normalized current. 47 As shown in Figure S11, the highest ECSA normalized current density of ANCO-3 indicates that Co doping can improve the samples' intrinsic electrocatalytic activity, which is consistent with the XPS analysis.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…Over the past decade, great efforts have been put into the study of single-atom catalysts, which possess an atomic dispersion of 100% to achieve full utilization of active metal atoms, which is remarkably effective to reduce the consumption of precious metals. Nevertheless, most supports beyond metal oxides are chemically unstable in the oxidizing atmosphere, such as carbon, metal sulfides, and so on. Consequently, metal oxide-supported single-atom (single-atom/metal oxide) catalysts are essential to catalytic CO oxidation.…”
Section: Introductionmentioning
confidence: 99%
“… where Δ j is the current density (mA cm –2 ), V is the potential, and C s is the standard specific capacitance ( C s −0.04 mF cm –2 ). 25 Pd(II)IPA/GrCC, Co(II)IPA/GrCC, and Ni(II)IPA/GrCC hybrid complexes involve ECSA values of 0.15, 0.385, and 0.152 m 2 g –1 , respectively. The high surface area of the electrocatalysts is due to the presence of the porous and weaved textile framework of the carbon cloth.…”
Section: Resultsmentioning
confidence: 99%
“…The linear plot (Figure a) revealed that the electrocatalytic process is a diffusion-controlled process. The current is due to the facile electron flow at the electrode/electrolyte interface. where Δ j is the current density (mA cm –2 ), V is the potential, and C s is the standard specific capacitance ( C s −0.04 mF cm –2 ) . Pd­(II)­IPA/GrCC, Co­(II)­IPA/GrCC, and Ni­(II)­IPA/GrCC hybrid complexes involve ECSA values of 0.15, 0.385, and 0.152 m 2 g –1 , respectively.…”
Section: Resultsmentioning
confidence: 99%